15N-Urea Efficiency in Maize as Influenced by Humic Substances and Urease Inhibitors Treatments. Issue 2 (19th January 2019) - Rinaldi, Luís Felipe; Garcia, Pedro Lopes; Sermarini, Renata Alcarde; Trivelin, Paulo Cesar Ocheuze
ABSTRACT: Urea treated with urease inhibitors (UI) in association with humic substances (HS) is expected to improve urea efficiency by reducing ammonia losses and also provide the benefits of HS such as improve nitrogen (N) recovery by plants. Ammonia volatilization (AV), 15 N recovery efficiency in the soil (NRE) and 15 N use efficiency (NUE) were evaluated in maize ( Zea mays L.) in a greenhouse pot trial. Treatments consisted of 15 N-urea treated with UI (0, 0.4% boron (B) +0.15% copper (Cu), 0.64% B, and NBPT (N-(n-butyl) thiophosphoric triamide)) and three levels of HS (0%, 0.6%, and 1.2%). A control treatment (without N) was also included. N treatments were applied at V4 (vegetative leaf stage 4) on soil surface. HS was not efficient on AV reduction, NBPT had the greatest reduction in AV, and B had higher efficiency on AV reduction than Cu. At V8 (vegetative leaf stage 8), NBPT had the greatest NUE followed by B. At VT (tassel fully emerged), NUE from urea treated with NBPT reduced when increased levels of HS, and NBPT had the greatest NRE. UI in association with HS treated-urea does not reduce AV and it does not improve NUE by maize in vegetative stages.